Analisis Struktur Perekonomian Berdasarkan Pendekatan Shift Share di Surakarta Tahun 2008-2013 - Pertiwi, Ari Indah; , Dr. Didit Purnomo, M.Si (2015)
Economic growth has changed the structure of the economy. Structural transformation is a process of change in the economic structure of the primary sector secondary kesektor, as was the case in Surakarta. Changes in the structure or economic transformation from traditional to modern in general can be seen as a change related to the shift in the composition of employment and contribution to GDP in a wilayah.Tujuan of this study is to analyze the economic structure of the area as well as a shift in sectors seen from the absorption of power employment and contribution to GDP in Surakarta in the period 2008-2013. The data used in this analysis is secondary data obtained from statisti Central Agency (BPS). To view the structure of the economy in the period of 2008-2013 Surakarta used tool shift share analysis. Results of the shift share analysis shows that the shift of labor, from the agricultural sector showed a negative amount of labor as much as 0.27% to 11.37% of industrial sector. And the contribution to GDP of agricultural sector amounted to 1885.56 million to the industrial sector amounted to 785,260.00 million. In Surakarta this means there has been a change in the economic structure of the traditional into the modern economy in Surakarta.